Alterations of large‐scale functional network connectivity in patients with infantile esotropia before and after surgery - Jianlin Guo; Yuanyuan Chen; Wen Liu; Lijuan Huang; Di Hu; Yanqiu Lv; Huiying Kang; Ningdong Li; Yun Peng (Brain and Behavior, 2023)
Abstract Background Growing evidences have indicated neurodevelopmental disorders in infantile esotropia (IE). However, few studies have analyzed the characteristics of large‐scale functional networks of IE patients or their postoperative network‐level alterations. Methods Here, individuals with IE (n = 32) and healthy subjects (n = 30) accomplished the baseline clinical examinations and resting‐state MRI scans. A total of 17 IE patients also underwent corrective surgeries and completed the longitudinal clinical assessments and resting‐state MRI scans. Linear mixed effects models were applied for cross‐sectional and longitudinal network‐level analyses. Correlation analysis was performed to assess the relationship between longitudinal functional connectivity (FC) alterations and baseline clinical variables. Results In cross‐sectional analyses, network‐level FC were apparently aberrant in IE patients compared to controls. In longitudinal analyses, intra‐ and internetwork connectivity were observed with significant alterations in postoperative IE patients compared to the preoperative counterparts. Longitudinal FC changes are negatively correlated to the age at surgery in IE. Conclusions Obviously, altered network‐level FC benefiting from the corrective surgery serves as the neurobiological substrate of the observed improvement of stereovision, visuomotor coordination, and emotional management in postoperative IE patients. Corrective surgery should be performed as early as possible to obtain more benefits for IE in brain function recovery.